Glucose-Sensing in the Reward System - Koekkoek, Laura L.; Mul, Joram D.; la Fleur, Susanne E. (Frontiers in Neuroscience, 2017)
Glucose-sensing neurons are neurons that alter their activity in response to changes in extracellular glucose. These neurons, which are an important mechanism the brain uses to monitor changes in glycaemia, are present in the hypothalamus, where they have been thoroughly investigated. Recently, glucose-sensing neurons have also been identified in brain nuclei which are part of the reward system. However, little is known about the molecular mechanisms by which they function, and their role in the reward system. We therefore aim to provide an overview of molecular mechanisms that have been studied in the hypothalamic glucose-sensing neurons, and investigate which of these transporters, enzymes and channels are present in the reward system. Furthermore, we speculate about the role of glucose-sensing neurons in the reward system.